NASKAH MENDU SANGGAR MATAN PEKANBARU: ANALISIS INTERTEKSTUAL - Yuliana Yuliana; Syafrial Syafrial; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: his study discusses the Mendu Manuscript of Sanggar Matan Pekanbaru: Intertextual Analysis. The background of this study is currently the Mendu Manuscript originating from Bunguran and Natuna Island, Riau Islands Province. as cultural heritage is rarely performed again in the community, but in recent years Sanggar Matan Pekanbaru as one of the large studios in Riau began to focus their performances on Mendu Manuscripts. Monda Gianes as the director and re-writer of the Mendu Manuscript using his own creative land. Purpose of this study is to intertextually describe the Sanggar Matan version of the Mendu Manuscript with the Mendu Manuscript version of Dewa Mendu's Hikayat. This research is descriptive qualitative research that describes and describes the results of the research conducted. Based on research, it is classified into 1) plot / plot, 2) characterization, 3) dialogue, 4) background, 5) theme, 6) mandate, 7) technical guidance.Key Words: Mendu Manuscript, Sanggar Matan, Hikayat Dewa Mendu, Intertextual.